Serum Lipid Profile and Leptin Levels in Asthmatic Libyan Children - Ghwarsha, Enas K; Albadry, Agila A; Algazal, Najat; Algazal, Rabia; Elshaari, Farag A; Sheriff, Dhastagir Sultan (International Journal of Medical and Health Sciences Research, 2016)
Aim:To study lipid profile and leptin levels in non-obese Libyan children with asthma.. Materials and Methods:70 Libyan children from Pediatrics Department, Faculty of Medicine, Benghazi University, Benghazi, Libya were included for the present study (from 2013 to 2014). Group I formed the normal control group (N: 30 Children) and Group II is 40 Libyan children with asthma. Their age group varied from 4 to 12 years old. Serum lipid profile and leptin were measured by routine standard methods. Results and discussion: The Libyan children with asthma showed an increase in serum total cholesterol, LDL cholesterol, VLDL cholesterol, HDL cholesterol and triglycerides. Serum Leptin levels did not show marked changes between the two groups. The presence of hypercholesterolemia could be a triggering factor for generation of proinflammatory response in these children. Though leptin levels did not show marked response further studies may be necessary to study the role of leptin in obese asthmatic Libyan children.